Parent, peer, and executive function relationships to early adolescent e-cigarette use: A substance use pathway?. (March 2015) - Pentz, Mary Ann; Shin, HeeSung; Riggs, Nathaniel; Unger, Jennifer B.; Collison, Katherine L.; Chou, Chih-Ping
Abstract: Introduction: Little is known about influences on e-cigarette use among early adolescents. This study examined influences that have been previously found to be associated with gateway drug use in adolescents: demographic (age, gender, ethnicity, free lunch), social contextual influences of parents and peers, and executive function deficits (EF). Methods: A cross-sectional survey was administered to 410 7th grade students from two diverse school districts in Southern California (M age; = 12.4 years, 48.3% female, 34.9% on free lunch (low socioeconomic status), 45.1% White, 25.4% Hispanic/Latino, 14.9% Mixed/bi-racial.) Logistic regression analyses examined influences of demographic, parent e-cigarette ownership and peer use, and EF on lifetime e-cigarette, and gateway drug use (cigarette and/or alcohol use). Results: Lifetime use prevalence was 11.0% for e-cigarettes, 6.8% for cigarettes, and 38.1% for alcohol. Free lunch and age were marginally related to e-cigarette use (p < .10). Parent e-cigarette ownership was associated with use of all substances, while peer use was associated with gateway drug use (p's < .05-.001). EF deficits were associated with use of all substances five times more likely than others to use e-cigarettes and over twice as likely to use gateway drugs. Conclusions: E-cigarette and gateway drug use may have common underlying risk factors in early adolescence, including parent and peer modeling of substance use, as well as EF deficits. Future research is needed to examine longitudinal relationships of demographics, parent and peer modeling, and EF deficits to e-cigarette use in larger samples, trajectories of e-cigarette use compared to use of other substances, and the potential of EF skills training programs to prevent e-cigarette use. Highlights: Lifetime e-cigarette use was almost twice the use of cigarettes in early adolescents. Executive function (EF) deficits related to e-cigarette, cigarette, and alcohol use. EF deficits were more important than demographic, peer, or parent influences on use. Suggests adolescent drug use prevention programs should include EF skills training.